Pulmonary artery flotation catheter combined with pump-controlled retrograde trial off as a trial for weaning from veno-arterial extracorporeal membrane oxygenation: a case report. (September 2019) - Xu, Ying; Gu, Qin
Background: The Swan–Ganz catheter is a reliable method used to monitor hemodynamics in intensive care units. Pump-controlled retrograde trial off is a new weaning test for veno-arterial extracorporeal membrane oxygenation in recent years. The objective of this report is to describe a case in which pulmonary artery flotation catheter hemodynamic monitoring in combination with pump-controlled retrograde trial off was sufficient for veno-arterial extracorporeal membrane oxygenation weaning. Methods: We report the case of an adolescent patient with acute heart failure due to acute severe myocarditis in veno-arterial extracorporeal membrane oxygenation, intra-aortic balloon pump, and pulmonary artery flotation catheter hemodynamic monitoring. Results: Pulmonary artery flotation catheter hemodynamic monitoring pre- and post pump-controlled retrograde trial off was successfully proven to predict decannulation success. The patient was weaned off of the extracorporeal membrane oxygenation, intra-aortic balloon pump, and pulmonary artery flotation catheter. His cardiac function gradually recovered, and he was discharged. Conclusion: The combination of pulmonary artery flotation catheter hemodynamic monitoring and pump-controlled retrograde trial off can increase the possibility of veno-arterial extracorporeal membrane oxygenation successful decannulation.